New challenges of geography in cultural and institutional association within the European higher education area - Lorber, Lučka (Journal for Geography, 2008)
University of Maribor has in the last few years been an active partner in establishing and encouraging regional cooperation within Danube Rector’s network and Alpe-Adria network. Geographers have helped form the policy and concepts of regional partnership and connecting of spatial projects and initiatives, particularly in the regions of Central Europe and Western Balkans. An example of good practice is the Central European network GEOREGNET, which enables mobility of professors and students and contributes to the understanding among people and cooperation in higher education. The new challenges of Geography in the establishment of Euroregions and formation of a European cultural area represent a new understanding of the importance of creating a network of institutional cooperation and education of geographers. Research and pedagogical work in the field of Geography enable development and implementation of internationally comparable post-graduate study programmes and research programmes. With the establishment of University Centre for Euro-Mediterranean Studies, Slovenia has assumed the responsibility and an active role in encouraging the cooperation of higher education institutions in order to accomplish the goals of the European higher education area and strengthen intercultural understanding, not only between the countries of Euro-Mediterranean region, but also in the sense of global regional associations.